THE SIGNIFICANCE OF VENDIAN FAUNA FROM PODOLIA FOR MAKING COMMON SCALE OF VEND - MIENASOVA, A. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
In article is talking about boards of vendian system, discription and analysis organic world (which take places in mogilev's and kanilov's time). It's propouse vendian saction of Podoliya take as a model Vendian system.